Learner Errors In Writing Recount Text Made By Students Of SMP N 1 Penawangan - Syuhada, Shonnifaul; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This study aims at describing the errors made by the second grade students of SMP Negeri 1 Penawangan in their written recount text; identify the types of lexical errors, syntactical errors and discourse errors; describing the frequency of each type of errors; explain the dominant type of error; identify the source of error and explain the proposed remedial teaching for the students. The type of this research is descriptive qualitative research. In collecting the data, the writer uses elicitation technique and documentation. There are four steps to collect data, namely: the writer gets the data of English composition made by the students from the teacher, the writer reads every composition accurately, the writer writes again all of the erroneous sentences of the student's composition, the writer writes all the erroneous sentences into a list and used them as the data. The collected data are analyzed by using Dulay, Burt and Krashen classification of errors theory, Slamet the frequency of type of error theory and Brown source of errors theory. The results of the research show that the second grade students of SMP Negeri 1 Penawanganstill make 405 errors in their compositions. The writer finds that from 405 data, there are three classifications of error based on the combination of linguistic category and surface strategy taxonomy. There are lexical errors consist of 23,70% which covers: false friend 2,22%, literal translation18,02%, and use wrong spelling 3,46%. Errors on syntactical errors consist of 76,3% covering: omission 12,1%, Misselection 0,99%, Tenses 51,11%, misordering 11,60%, sentence pattern 0, 49%. The highest frequency of errors that the researcher found is the uses of V1 in state of V2 in writing recount text. There are 53 or 13, 09% errors that the writer found from the total errors. The researcher also finds 2 dominant sources error, namely: interlingual transfer and intralingual transfer.